ANALISIS KEBUTUHAN TERHADAP BAHASA ARAB DALAM PENGEMBANGAN PARIWISATA HALAL DI BANDA ACEH DAN ACEH BESAR - Maimunsyah Rosalinda (Universitas Jabal Ghafur, 2019)
The cities of Banda Aceh and Aceh Besar, the province of Aceh on the western tip of the Sumatra, is one of the halal tourism destinations in Indonesia. Development or promotion that is certainly not inseparable from several important elements, including elements of language. The purpose of this study is as an initial step to find out the need for Arabic in developing Halal tourism sector in Banda Aceh and Aceh Besar, knowing the need for Arabic for halal tourism promotion and services in Banda Aceh and Aceh Besar and knowing the steps for tourism development Halal taken by the Tourism office. Data collection techniques in this study were conducted by interview and questionnaire. The results of this study are that Arabic is needed in efforts to develop halal tourism in Aceh and Aceh Besar. . Keywords: Language; Arab; Tourism; Halal